Sol-gel TiO2 colloidal suspensions and nanostructured thin films: structural and biological assessments. (5th January 2018) - Procopio, Elsa Quartapelle; Colombo, Valentina; Santo, Nadia; Sironi, Angelo; Lenardi, Cristina; Maggioni, Daniela
Abstract: The role of substrate topography in phenotype expression of in vitro cultured cells has been widely assessed. However, the production of the nanostructured interface via the deposition of sol-gel synthesized nanoparticles (NPs) has not yet been fully exploited. This is also evidenced by the limited number of studies correlating the morphological, structural and chemical properties of the grown thin films with those of the sol-gel 'brick' within the framework of the bottom-up approach. Our work intends to go beyond this drawback presenting an accurate investigation of sol-gel TiO2 NPs shaped as spheres and rods. They have been fully characterized by complementary analytical techniques both suspended in apolar solvents, by dynamic light scattering (DLS) and nuclear magnetic resonance (NMR) and after deposition on substrates (solid state configuration) by transmission electron microscopy (TEM) and powder x-ray diffraction (PXRD). In the case of suspended anisotropic rods, the experimental DLS data, analyzed by the Tirado-Garcia de la Torre model, present the following ranges of dimensions: 4–5 nm diameter (∅) and 11–15 nm length (L). These results are in good agreement with that obtained by the two solid state techniques, namely 3.8(9) nm ∅ and 13.8(2.5) nm L from TEM and 5.6(1) ∅ and 13.3(1) nm L from PXRD data. To prove the suitability of the supported sol-gel NPs for biological issues, spheres and rods have been separately deposited on coverslips. The cell response has been ascertained by evaluating the adhesion of the epithelial cell line Madin–Darby canine kidney. The cellular analysis showed that titania films promote cell adhesion as well clustering organization, which is a distinguishing feature of this type of cell line. Thus, the use of nanostructured substrates via sol-gel could be considered a good candidate for cell culture with the further advantages of likely scalability and interfaceability with many different materials usable as supports.